تعرض الطلبة الجامعيين للمنصات التلفزيونية الرقمية واتجاهاتهم نحوها - ابتسام بن حامد; رانيا رمضاني (جامعة الوادي - University of Eloued, 2025)
"تناولت هذه الدراسة موضوع المنصات التلفزيونية الرقمية من خلال التركيز على مدى تعرض الطلبة الجامعيين لها واتجاهاتهم نحوها، وذلك في ظل التحولات المتسارعة التي يشهدها مجال الإعلام، وتهدف هذه الدراسة الى قياس تعرض الطلبة الجامعيين نحو المنصات التلفزيونية الرقمية وتحليل اتجاهاتهم، من حيث معدل الإستخدام ودوافع المشاهدة ومستوى الرضا،وإنعكاس ذلك على سلوكهم الإعلامي . كما تكمن أهمية الدراسة في فهم مدى استخدام الطلبة للمنصات التلفزيونية الرقمية والعوامل التي تسهم في تفضيلاتهم وأنماط استهلاكهم للمحتوى. وقد اعتمدت الدراسة على المنهج المسحي كونه المنهج المناسب لدراسة، بالاعتماد على أداة الاستبيان، وتم تطبيق الدراسة على العينة الطبقية المكونة من 96 طالباً وطالبة من مختلف الكليات في الجامعة وبعد إجراء الدراسة توصلنا الى مجموعة من النتائج تمثلت أهمها في: - منصة شاهد Shahid من أكثر المنصات التلفزيونية الرقمية استخداما لدى الطلبة الجامعيين لما تتضمنه من محتوى حصري و عربي مجاني يتماشى مع اهتماماتهم الثقافية والاجتماعية. - الدافع الاول وراء اقبال الطلبة على هذه المنصات هو سعيهم نحو محتوى متنوع وحصري يتجاوز مايقدمه التلفزيون التقليدي من حيث الشكل والمضمون . - يلجأ الطلبة الى هذه المنصات كونها وسيلة للترفيه و تعديل المزاج وتخفيف التوتر الناتج عن الدراسة - تحقق المنصات رضا كبير لدى الطلبة نتيجة تلبية اهتماماتهم الفكرية والثقافية . "This study addressed the topic of digital television platforms by focusing on the extent of university students' exposure to them and their attitudes towards them, in light of the rapid transformations in the field of media, and this study aims to measure students' attitudes towards digital television platforms and analyze their attitudes towards them in terms of usage rate, viewing motives, level of satisfaction, and the reflection of this on their media behavior. The importance of the study lies in understanding the extent of students' use of digital TV platforms and the factors that contribute to their preferences and content consumption patterns. The study relied on the survey method as the appropriate method for a study, relying on the questionnaire tool, and the study was applied to a simple random sample consisting of 96 male and female students from various university majors. After conducting the study, we came up with a set of results, the most important of which are as follows: The Shahid platform is one of the most used digital TV platforms- amonguniversity students because it includes exclusive and free Arabic content in line with their cultural and social interests - The first motive behind students’ interest in these platforms is their -quest for diverse and exclusive content that exceeds what traditional television offers in terms of form and content Students resort to these platforms as a means of entertainment, mood- modification and relieving stress resulting from the study The platforms achieve great satisfaction among students as a result of- meeting their intellectual and cultural interests "
مذكرة ماستر قسم اعلام واتصال تخصص سمعي بصري
Keywords: الإتجاهات; التعرض; المنصات التلفزيونية الرقمية; DigitalTelevisionPlatforms; Exposure; Attitudes